2018
DOI: 10.1007/s10086-018-1702-3
|View full text |Cite
|
Sign up to set email alerts
|

Properties of flat-pressed wood plastic composites as a function of particle size and mixing ratio

Abstract: This paper presents the effects of particle size and mixing ratio on the properties including physical, mechanical, and decay resistance of wood plastic composites (WPCs). In addition, it also presents the effects of immersion temperatures on water absorption (WA) and thickness swelling (TS) of the WPCs. WPCs with a thickness of 6 mm were fabricated from Albizia richardiana King & Prain wood particles and recycled polyethylene terephthalate (PET) by the flat-press method. To prepare the WPCs, two different woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…In addition, the moisture content of the WPCs decreased with decreasing WF size, and the WPCs with less than 60 mesh WFs (WPC S60 ) exhibited the lowest moisture content (0.90%). This trend is similar to that reported by Rahman et al [45] for composites made of recycled polyethylene terephthalate (PET) and different sizes of WFs. Rahman et al [45] found that there were more voids in the WPCs that contained larger WFs, which made it easier for moisture to penetrate through the openings of the composites.…”
Section: The Physical and Flexural Properties Of The Wpcssupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, the moisture content of the WPCs decreased with decreasing WF size, and the WPCs with less than 60 mesh WFs (WPC S60 ) exhibited the lowest moisture content (0.90%). This trend is similar to that reported by Rahman et al [45] for composites made of recycled polyethylene terephthalate (PET) and different sizes of WFs. Rahman et al [45] found that there were more voids in the WPCs that contained larger WFs, which made it easier for moisture to penetrate through the openings of the composites.…”
Section: The Physical and Flexural Properties Of The Wpcssupporting
confidence: 91%
“…This trend is similar to that reported by Rahman et al [45] for composites made of recycled polyethylene terephthalate (PET) and different sizes of WFs. Rahman et al [45] found that there were more voids in the WPCs that contained larger WFs, which made it easier for moisture to penetrate through the openings of the composites. Moreover, the WPCs with the smallest WFs (WPC S60 ) showed the lowest MOR (39 MPa) and MOE (2.3 GPa) values among WPCs with different sizes of WFs.…”
Section: The Physical and Flexural Properties Of The Wpcssupporting
confidence: 91%
See 2 more Smart Citations
“…A general rule for mixing is that large pieces of wood shavings should be matched with large pieces of thermoplastic, and small pieces of shavings matched with small pieces of thermoplastic. Increasing the fiber aspect ratio can produce a larger contact area between the fiber and plastic matrix, which is able to improve the composites’ performance [ 55 , 56 ]. Qi [ 31 , 57 ] prepared cotton stalk–HDPE-oriented composites.…”
Section: Processing Technology Of Thermoplastic-bonded Wood-based Panelsmentioning
confidence: 99%